Concepção e avaliação de diferentes sistemas de aquecimento para suínos recém-nascidos - Sulzbach, Jéssica Juliane (2016)
The pork consumption worldwide has increased in last years, with this improving the production system has been increasingly required for any activity, resulting in changes in the cost matrix, which involves energy matrix. One of the very important factors in the production of piglets system is the thermal comfort of newborn pigs, requiring the additional heating these to optimize production. The heating current system uses incandescent lamps and, in some cases, heated floors with electrical resistances. Incandescent bulbs, because they have low energy efficiency are being replaced, and in the case of Brazil by law should be extinct by the year 2016. This study analyzed different types of heating systems, PA - with floor heating shelters with circulating hot water, where the primary water heating occurred for a hybrid system (solar panels, biogas, GLP gas and electricity); LC - incandescent lamps type SPOT 40 W with black metal plate on a side of the shelter; and L - incandescent lamps type SPOT 40 W without metal plate. Shelters heated with circulating water heated by floor (PA) had the highest average temperatures and the largest weight gain of piglets, providing better thermal comfort for the piglets and higher revenues from the sale of piglets.